Passions, Travel, and Cultural Participation—Intergenerational Transmission of Middle-Class Lifestyles - Magdalena Bielińska (Qualitative Sociology Review)
The article addresses the intergenerational transmission of a middle-class lifestyle in Poland. The analysis demonstrates mechanisms through which cultural practices are inherited in the context of leisure activities. The following categories of leisure activities were identified as being of particular interest: 1) passions, that is, the most pronounced leisure interests, including sport, 2) travel, 3) various forms of cultural participation, such as reading, visual and performing arts, or audiovisual content. The innovative research plan included reanalysis, revisits, and new in-depth interviews. The findings are based on a substantial corpus of qualitative empirical material, comprising 66 individual in-depth interviews. This material covers interviews conducted approximately twenty years before my research, new interviews with the same participants conducted subsequently, and interviews with their adult children. The aforementioned methodological procedures permitted comparisons over time and between generations. Middle-class parents proactively transmit values and practices to their children that are instrumental in maintaining their children’s social status. The effort to format lifestyle messages has significant implications for the long-term viability of this social structure segment in Poland. The analyses conducted indicate the cultural identity of the middle class and the stability of values and practices enacted in non-work and non-educational leisure time. Consequently, they are expected to yield tangible benefits in the professional and educational domains for subsequent generations. This represents the anticipated return on investment in leisure time for middle-class children.